Analisis Problematika Rumah Tangga dan Upaya Mencari Keadilan di Pengadilan Agama - Saifullah Saifullah (USRATUNA: Jurnal Hukum Keluarga Islam, 2025)
This article discusses domestic issues and the search for justice in Religious Courts in Indonesia. Domestic issues are defined as complex conflicts involving legal, social, economic, and psychological dimensions in marital and extended family relationships, which often lead to divorce. Religious courts serve as the primary institutions for resolving family disputes based on Islamic and national law, applying the principle of substantive justice. Although mediation is mandatory, its success rate is low due to high emotional tension and power imbalances. Data shows an increasing trend in divorce cases, indicating growing legal awareness among women. This article also offers concepts for family court reform, namely: the establishment of a Family Justice Center for integrated services, the revitalization of empathy-based mediation, the digitization of family law advocacy, gender perspective training for judges, and premarital and postmarital legal education. This reform is expected to strengthen the protection of women and children, improve the quality of decisions, and create a family court system that is more just, humane, and based on the values of maqashid sharia. With this holistic approach, it is hoped that domestic problems can be resolved not only formally through legal means, but also socially and psychologically in a just manner.